Top Management Team Characteristics and Firm Performance: A Test of Upper Echelons Theory in the Indonesian Tobacco Industry - Herlina Afriyanti; Henni Indriyani (CV. Era Digital Nusantara, 2024)
This study aims to examine and analyze the effect of Top Management Team (TMT) characteristics, measured through the variables of age, education level, and gender of the board of directors, on corporate financial performance within the tobacco industry. Grounded in the Upper Echelons Theory, this research focuses on PT HM Sampoerna Tbk as the object of study. The research sample consists of 36 observational data points obtained from the company's monthly financial reports during the 2021 to 2023 period. The data analysis techniques include descriptive statistics, classical assumption tests, and multiple linear regression analysis, accompanied by hypothesis testing (t-test and F-test). The partial test results (t-test) prove that the age variable of the directors has a significant negative effect on profitability (ROA), indicating that younger directors tend to be more adaptive. Conversely, the education level and gender diversity within the board of directors show a significant positive effect on the company's profitability. Furthermore, the simultaneous test results (F-test) confirm that the age, education, and gender of the directors collectively have a significant effect on financial performance, with an explanatory power (R-Square) of 61%. The conclusion of this study provides empirical support for the Upper Echelons Theory, demonstrating that top managerial demographic characteristics are crucial factors determining the effectiveness of strategic decision-making and the success of corporate financial performance amid industry dynamics